The signaling effects of fiscal announcements - Melosi, L; Morita, H; Rogantini Picco, A; Zanetti, F (University of Oxford, 2024)
Announcing a large fiscal stimulus may signal the government’s pessimism about the severity of a recession to the private sector, impairing the stabilizing effects of the policy. Using a theoretical model, we show that these signaling effects occur when the stimulus exceeds expectations and are more noticeable during periods of high economic uncertainty. Analysis of a new dataset of daily stock prices and fiscal news in Japan supports these predictions. We introduce a method to identify fiscal news with different degrees of signaling effects and find that such effects weaken or, in extreme cases, even completely undermine the stabilizing impact of fiscal policy.